PROBLEMS OF LEGAL REGULATION OF THE USE OF TRANSBOUNDARY WATER BODIES IN CENTRAL ASIA (Journal of actual problems of jurisprudence, 2020)
Given article analyses the causes of increasing problems of shared water use by transboundary riversin Central Asia. The existing complex problems of relations between the states of the region reduce theeffectiveness of individual states, the work of industries, the level of life safety, the existence of waterand terrestrial ecosystems. Water use in the region and the ability to control it is turning into a powerfulmechanism of economic and political pressure from some states of the Central Asian region. Accordingto the fact that on a number of issues the governments of Central Asia cannot come to a consensus, itis proposed to use the experience of Europe. It is noted that in spite of the development of contractualinternational water legislation, issues of joint water use are exacerbated in practice and develop intointernational conflicts. In order to avoid conflicts, the author believes that despite the active position ofKazakhstan in international politics and the quantity and quality of agreements concluded by him on theuse of transboundary opening facilities, one should consider options for using own facilities and reducethe consumption of transboundary rivers. It is also proposed to continue the policy of hydro-diplomacybased on economical and environmentally friendly water use.Key words: water law, water security, transboundary water bodies, shared water use, legal regulation.